Ozone-Forming Potential of Reformulated Gasoline - National Research Council (The National Academies Press, 1999)
The Committee on Ozone-Forming Potential for Reformulated Gasoline was asked whether the existing body of scientific and technical information is sufficient to permit a robust evaluation and comparison of the emissions from motor vehicles using different reformulated gasolines based on their ozone-forming potentials and to assess the concomitant impact of that approach on air-quality benefits of the use of oxygenates within the RFG program. As part of its charge, the committee was asked to consider (1) the technical soundness of various approaches for evaluating and comparing the relative ozone-forming potentials of RFG blends, (2) technical aspects of various air-quality issues related to RFG assessment, and (3) the sensitivity of evaluations of the relative ozone-forming potentials to factors related to fuel properties and the variability of vehicle technologies and driving patterns.
Keywords: Environment and Environmental Studies

Evaluating Vehicle Emissions Inspection and Maintenance Programs - Transportation Research Board; National Research Council (The National Academies Press, 2001)
Emissions inspection and maintenance (I/M) programs subject vehicles to periodic inspections of their emission control systems. Despite widespread use of these programs in air-quality management, policy makers and the public have found a number of problems associated with them. Prominent among these issues is the perception that emissions benefits and other impacts of I/M programs have not been evaluated adequately. Evaluating Vehicle Emissions Inspection and Maintenance Programs assesses the effectiveness of these programs for reducing mobile source emissions. In this report, the committee evaluates the differences in the characteristics of motor vehicle emissions in areas with and without I/M programs, identifies criteria and methodologies for their evaluation, and recommends improvements to the programs. Most useful of all, this book will help summarize the observed benefits of these programs and how they can be redirected in the future to increase their effectiveness.
Keywords: Environment and Environmental Studies; Transportation and Infrastructure

Modeling Mobile-Source Emissions - Transportation Research Board; National Research Council (The National Academies Press, 2000)
The Mobile Source Emissions Factor (MOBILE) model is a computer model developed by the U.S. Environmental Protection Agency (EPA) for estimating emissions from on-road motor vehicles. MOBILE is used in air-quality planning and regulation for estimating emissions of carbon monoxide (CO), volatile organic compounds (VOCs), and nitrogen oxides (NOx) and for predicting the effects of emissions-reduction programs. Because of its important role in air-quality management, the accuracy of MOBILE is critical. Possible consequences of inaccurately characterizing motor-vehicle emissions include the implementation of insufficient controls that endanger the environment and public health or the implementation of ineffective policies that impose excessive control costs. Billions of dollars per year in transportation funding are linked to air-quality attainment plans, which rely on estimates of mobile-source emissions. Transportation infrastructure decisions are also affected by emissions estimates from MOBILE. In response to a request from Congress, the National Research Council established the Committee to Review EPA's Mobile Source Emissions Factor (MOBILE) Model in October 1998. The committee was charged to evaluate MOBILE and to develop recommendations for improving the model.
Keywords: Environment and Environmental Studies

State and Federal Standards for Mobile-Source Emissions - National Research Council (The National Academies Press, 2006)
Emissions from mobile sources contribute significantly to air pollution in the United States. Such sources include cars and light- and heavy-duty trucks; diesel-powered cranes, bulldozers, and tractors; and equipment such as lawnmowers that run on small gasoline engines. The role of state versus federal government in establishing mobile-source emissions standards is an important environmental management issue. With this in mind, Congress called on EPA to arrange an independent study of the practices and procedures by which California develops separate emissions standards from the federal government and other states choose to adopt the California standards. The report provides an assessment of the scientific and technical procedures used by states to develop or adopt different emissions standards and a comparison of those policies and practices with those used by EPA. It also considers the impacts of state emissions standards on various factors including compliance costs and emissions. The report concludes that, despite the substantial progress in reducing emissions from mobile sources nationwide, more needs to be done to attain federal air-quality standards in many parts of the country. Additionally, California should continue its pioneering role in setting emissions standards for cars, trucks, and off-road equipment.
Keywords: Transportation and Infrastructure; Environment and Environmental Studies

Report by the Committee on Motor Vehicle Emissions (The National Academies Press, 1973)
Keywords: Environment and Environmental Studies

Aircraft and Airport-Related Hazardous Air Pollutants: Research Needs and Analysis - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2008)
TRB’s Airport Cooperative Research Program (ACRP) Report 7: Aircraft and Airport-Related Hazardous Air Pollutants: Research Needs and Analysis examines the state of the latest research on aviation-related hazardous air pollutants emissions and explores knowledge gaps that existing research has not yet bridged.
Keywords: Transportation and Infrastructure

Guidance for Estimating Airport Construction Emissions - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Airport Cooperative Research Program (ACRP) Report 102: Guidance for Estimating Airport Construction Emissions provides guidance and an interactive electronic tool—the Airport Construction Emissions Inventory Tool—to assist airports and other stakeholders in developing airport construction emissions inventories.The Airport Construction Emissions Inventory Tool (ACEIT) is included in CD-ROM format with the printed version of the report.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

The Ongoing Challenge of Managing Carbon Monoxide Pollution in Fairbanks, Alaska: Interim Report - Transportation Research Board; National Research Council (The National Academies Press, 2002)
Carbon monoxide (CO) is a toxic air pollutant produced largely from vehicle emissions. Breathing CO at high concentrations leads to reduced oxygen transport by hemoglobin, which has health effects that include impaired reaction timing, headaches, lightheadedness, nausea, vomiting, weakness, clouding of consciousness, coma, and, at high enough concentrations and long enough exposure, death. In recognition of those health effects, the U.S. Environmental Protection Agency (EPA), as directed by the Clean Air Act, established the health-based National Ambient Air Quality Standards (NAAQS) for CO in 1971.Most areas that were previously designated as "nonattainment" areas have come into compliance with the NAAQS for CO, but some locations still have difficulty in attaining the CO standards. Those locations tend to have topographical or meteorological characteristics that exacerbate pollution. In view of the challenges posed for some areas to attain compliance with the NAAQS for CO, congress asked the National Research Council to investigate the problem of CO in areas with meteorological and topographical problems. This interim report deals specifically with Fairbanks, Alaska. Fairbanks was chosen as a case study because its meteorological and topographical characteristics make it susceptible to severe winter inversions that trap CO and other pollutants at ground level.
Keywords: Environment and Environmental Studies

Airport Air Quality Management 101 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's Airport Cooperative Research Program (ACRP) Research Report 185: Airport Air Quality Management 101 introduces airport employees who are not environmental specialists to airport air quality issues. Airport air quality management is highly complex and technical, with many different stakeholders, including the local community and local, state, and federal regulators.Larger airports have dedicated environmental experts; however, at most airports, environmental management is carried out by employees who are engaged in other aspects of airport operations or provide oversight of external environmental consultants who are executing the work.This report is accompanied by ACRP WebResource 4: Airport Air Quality Resource Library.
Keywords: Transportation and Infrastructure

Options for Reducing Lead Emissions from Piston-Engine Aircraft - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Small gasoline-powered aircraft are the single largest emitter of lead in the United States, as other major emission sources such as automobile gasoline have been previously addressed. A highly toxic substance that can result in an array of negative health effects in humans, lead is added to aviation gasoline to meet the performance and safety requirements of a sizable portion of the country’s gasoline-powered aircraft.Significantly reducing lead emissions from gasoline-powered aircraft will require the leadership and strategic guidance of the Federal Aviation Administration (FAA) and a broad-based and sustained commitment by other government agencies and the nation’s pilots, airport managers, aviation fuel and service suppliers, and aircraft manufacturers, according to a congressionally mandated report from the National Academies of Sciences, Engineering, and Medicine.While efforts are underway to develop an unleaded aviation fuel that can be used by the entire gasoline-powered fleet, the uncertainty of success means that other steps should also be taken to begin reducing lead emissions and exposures, notes the report, titled TRB Special Report 336: Options for Reducing Lead Emissions from Piston-Engine Aircraft.Piston-engine aircraft are critical to performing general aviation (GA) functions like aerial observation, medical airlift, pilot training, and business transport. Other GA functions, such as crop dusting, aerial firefighting, search and rescue, and air taxi service, have particular significance to communities in rural and remote locations.Accompanying the report is a three-page highlight summary that provides a condensed version of the findings.
Keywords: Transportation and Infrastructure

Rethinking the Ozone Problem in Urban and Regional Air Pollution - National Research Council (The National Academies Press, 1991)
Despite more than 20 years of regulatory efforts, concern is widespread that ozone pollution in the lower atmosphere, or troposphere, threatens the health of humans, animals, and vegetation. This book discusses how scientific information can be used to develop more effective regulations to control ozone. Rethinking the Ozone Problem in Urban and Regional Air Pollution discusses:
Keywords: Environment and Environmental Studies

Predicting Air Quality Effects of Traffic-Flow Improvements: Final Report and User's Guide - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 535: Predicting Air Quality Effects of Traffic-Flow Improvements: Final Report and User’s Guide provides a recommended methodology to predict the long- and short-term mobile source emission impacts of traffic-flow improvement projects. Guidance is provided to evaluate the magnitude, scale, and duration of such impacts for a variety of representative urbanized areas. The report evaluates varying strategic approaches used to develop methodologies for estimating the impacts of traffic-flow improvement projects on mobile source emissions, reviews advanced methodologies used by leading metropolitan planning agencies, and offers suggestions to improve conventional travel models.
Keywords: Transportation and Infrastructure

Air Quality Management in the United States - National Research Council (The National Academies Press, 2004)
Managing the nation’s air quality is a complex undertaking, involving tens of thousands of people in regulating thousands of pollution sources. The authors identify what has worked and what has not, and they offer wide-ranging recommendations for setting future priorities, making difficult choices, and increasing innovation. This new book explores how to better integrate scientific advances and new technologies into the air quality management system. The volume reviews the three-decade history of governmental efforts toward cleaner air, discussing how air quality standards are set and results measured, the design and implementation of control strategies, regulatory processes and procedures, special issues with mobile pollution sources, and more. The book looks at efforts to spur social and behavioral changes that affect air quality, the effectiveness of market-based instruments for air quality regulation, and many other aspects of the issue. Rich in technical detail, this book will be of interest to all those engaged in air quality management: scientists, engineers, industrial managers, law makers, regulators, health officials, clean-air advocates, and concerned citizens.
Keywords: Environment and Environmental Studies; Transportation and Infrastructure

Review of the Research Strategy for Biomass-Derived Transportation Fuels - National Research Council (The National Academies Press, 1999)
The Office of Fuels Development (OFD), a component of the U.S. Department of Energy's (DOE) Office of Transportation Technologies, manages the federal government's effort to make biomass-based ethanol (bioethanol) and biodiesel a practical and affordable alternative to gasoline. Through the National Biomass Ethanol Program, the OFD is overseeing key research and development (R&D) and industry-government partnerships for the establishment of a cellulosic biomass ethanol industry. Cellulosic biomass resources being investigated include agronomic and forest crop residues, woody crops, perennial grasses, and municipal wastes. Starch-based sources, such as cereal grains (e.g., corn grain), are not included in this program. The objective of the program is to promote the commercialization of enzyme-based technologies to produce cost-competitive bioethanol for use as transportation fuel. The OFD requested that the National Research Council estimate the contribution and evaluate the role of biofuels (biomass-derived ethanol and biodiesel) as transportation fuels in the domestic and international economies, evaluate OFD's biofuels strategy, and recommend changes in this strategy and the R&D goals and portfolio of the OFD in the near-term to midterm time frame (about 20 years). During this period, a number of complex, interacting factors, including advances in the technologies used to produce biofuels at a competitive cost, the elimination of tax incentives, advances in vehicle and engine technologies, growing concerns about solid waste disposal and air pollution, and global measures to reduce emissions of greenhouse gases to the atmosphere, will affect the position of biofuels in transportation fuel markets.
Keywords: Energy and Energy Conservation

Zero Emission Vehicles: Forecasting Fleet Scenarios and their Emissions Implications - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Vehicle electrification is one of the emerging and potentially disruptive technologies that are being considered to reduce emissions of criteria pollutants, mobile source air toxics (MSATs), and greenhouse gases (GHGs) from motor vehicles.The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 274: Zero Emission Vehicles: Forecasting Fleet Scenarios and their Emissions Implications analyzes a set of scenarios of infrastructure development, policy changes, and cost parameters, with a suite of 49 simulations across those scenarios conducted to assess their impact on nationwide zero emission vehicle (ZEV) adoption and the corresponding levels of exhaust emissions.The model used in the scenarios analysis is a consumer choice model that estimates future sales, populations, and fuel consumption of advanced technology vehicles (ATVs), including ZEVs.There is also a Power Point presentation accompanying the document.
Keywords: Transportation and Infrastructure

Managing Carbon Monoxide Pollution in Meteorological and Topographical Problem Areas - Transportation Research Board; National Research Council (The National Academies Press, 2003)
The regulation of carbon monoxide has been one of the great success stories in air pollution control. While more than 90 percent of the locations with carbon monoxide monitors were in violation in 1971, today the number of monitors showing violations has fallen to only a few, on a small number of days and mainly in areas with unique meteorological and topographical conditions.
Keywords: Environment and Environmental Studies

Input Guidelines for Motor Vehicle Emissions Simulator Model, Volume 2: Practitioners’ Handbook: Project Level Inputs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 210: Input Guidelines for Motor Vehicle Emissions Simulator Model, Volume 2: Practitioners’ Handbook: Project Level Inputs provides users of the Motor Vehicle Emissions Simulator (MOVES) model with tools to help estimate emissions from highway vehicles. Specifically, this handbook provides resource material on developing inputs for a project level of analysis using the Project Domain/Scale of MOVES.In addition to this report, NCHRP Web-Only Document 210 Volume 1: Practitioners’ Handbook: Regional Level Inputs provides resource material on developing inputs for a “regional” (county, multicounty, or state) level of application. NCHRP Web-Only Document 210 Volume 3: Final Report documents the research process for developing Volumes 1 and 2, and provides additional documentation not included in the handbook.Example dataset 1, example dataset 2, example dataset 3, and the MOVES tools are available for download. Please note that these files are large and may take some time to download.Software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively “TRB”) be liable for any loss or damage caused by the installation or operations of this product. TRB makes no representation or warrant of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Expanding Metropolitan Highways: Implications for Air Quality and Energy Use -- Special Report 245 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 1995)
TRB Special Report 245 - Expanding Metropolitan Highways: Implications for Air Quality and Energy Use reviews existing research on the links among highway capacity, traffic flow characteristics, travel demand, land use, vehicle emissions, air quality, and energy use in metropolitan areas; Identifies the conditions most likely to affect emissions and energy use; reviews the reliability of models and analyses that regional and state planning agencies use to forecast travel demand and land use, emission levels, and energy consumption; and recommends research strategies, modeling improvements, and data collection efforts to improve analytic capabilities.There are few more difficult or vexing local issues than the siting of a new highway or the expansion of an existing one. Local debates revolve around the trade-offs between easing congestion and increasing air pollution, noise, and sprawl. For many years, officials have attempted to respond to traffic congestion by adding highway capacity. Beyond meeting the public’s demand for roads, local and state officials view highway improvements as an integral part of their economic development strategies. Moreover, because vehicles in highly congested traffic operate inefficiently, it is believed that improving traffic flow would reduce emissions. On the other hand, opponents of new capacity contend that it induces more trips; that traffic in free-flow conditions also generates high emissions of some pollutants, particularly ozone precursors; and that the long-term effect of adding capacity is to support sprawling development. Examining these claims and counterclaims with technical evidence requires computer modeling of travel preferences, the resulting vehicle emissions, regional air quality, and the effects of new highway capacity on longterm land development.For decades, federal funding assistance created an incentive to build new highways. The Clean Air Act Amendments of 1990 represented an attempt to balance this incentive. Once these amendments became effective, metropolitan areas risked losing a share of their federal transportation funding if adding highway capacity would contribute to their failing to meet national air quality standards. Even though the regulations implementing the Clean Air Act Amendments require metropolitan areas to model the consequences of new capacity, the committee that conducted this study concluded that the existing analytical tools are inadequate for the task specified in the regulations. Whether new capacity is better or worse for air quality depends on local conditions. Relatively modest expansions probably have little effect, positive or negative, on air quality or land development in the urban periphery, whereas significant new capacity can, over a period of many years, contribute to increased travel, emissions, and low-density development patterns. Attempting to meet air quality goals through constraints on travel is an indirect policy measure. More direct benefits would accrue from improvements in vehicle technology, effective pricing or taxation of vehicle use, and more effective land development controls, although such measures are not without controversy and involve trade-offs of their own.
Keywords: Transportation and Infrastructure

Guide to Truck Activity Data for Emissions Modeling - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Report 909: Guide to Truck Activity Data for Emissions Modeling explores methods, procedures, and data sets needed to capture commercial vehicle activity, vehicle characteristics, and operations to assist in estimating and forecasting criteria pollutants, air toxics, and greenhouse gas emissions from goods and services movement.Goods movement is a vital part of the national economy, with freight movement growing faster than passenger travel. The growth in freight traffic is contributing to urban congestion, resulting in hours of delay, increased shipping costs, wasted fuel, and greater emissions of greenhouse gas and criteria pollutants. The limited national data on urban goods movement are insufficient for a thorough understanding of the characteristics of the trucks operating in metropolitan areas and the complex logistical chains that they serve.For instance, there are at least three different segments of urban freight—long haul, drayage, and pickup and delivery. It is believed that truck fleet characteristics differ between the segments, but only local registration data exist at a level of detail needed to support regional transportation plans, transportation improvement plans, and state implementation plans. The lack of data on all types of commercial trucks affects model estimation and results in inaccurate base year emissions inventories, limiting the ability to design and implement effective policies to reduce freight-related emissions.NCHRP Research Report 909 enumerates various sources of truck data and how they can be obtained and used to support emissions modeling.NCHRP Web-Only Document 210: Input Guidelines for Motor Vehicle Emissions Simulator Model (Porter et al., 2014a, 2014b, 2014c) provides guidance on developing local inputs to the MOVES mode. It covers all vehicle types, but is not specific to trucks. NCHRP Research Report 909 supplements NCHRP Web-Only Document 210 by describing the use of various data sources to obtain truck-specific inputs.Appendices A through G to NCHRP Research Report 909 are published as NCHRP Web-Only Document 261 and contain seven case studies that serve as the basis for much of the guidance provided in NCHRP Research Report 909.NCHRP Research Report 909 is also supplemented by three MS Excel files that contain data from the case studies:Case Studies #1 and #7Case Study #2Case Studies #3, #4, and #6
Keywords: Transportation and Infrastructure

The Future of Personal Transport in China: Summary of a Symposium, January 12, 2001 - National Research Council (The National Academies Press, 2001)
In August 1999 a delegation from the Chinese Academy of Engineering (CAE) visited The National Academies in Washington to discuss opportunities for collaboration on a study of the future of personal use vehicles in China. Barely motorized at present, China is confronted with the prospect of a massive increase in demand for automobiles. This is a summary of the first meeting of the Committee on the Future of Personal Use Vehicles in China, where the committee invited a group of experts to join some members of the committee to review the issues surrounding rapid motorization in China and the world experience in confronting similar problems in other countries. This symposium was designed to serve as the initial technical presentation to the committee and enabled some of the more difficult issues to be introduced by non-member experts in a setting outside of the committee room where they would be debated.

Controlling Hydrocarbon Emissions from Tank Vessel Loading (The National Academies Press, 1987)
Keywords: Environment and Environmental Studies

Appendices to ACRP Report 11: Guidebook on Preparing Airport GHG Emissions Inventories - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2008)
TRB’s Airport Cooperative Research Program (ACRP) Web-Only Document 2 contains appendices A through F to ACRP Report 11: Guidebook on Preparing Airport GHG Emissions Inventories. The appendices titles are as follows:Appendix A-Reasons for Developing GHG InventoriesAppendix B-Emissions and SourcesAppendix C-Methods for Calculating GHG EmissionsAppendix D-Methods for Calculating CO2 EquivalenciesAppendix E-Inventory Development ProtocolsAppendix F-Approaches Used in Airport Inventories Prepared to Date
Keywords: Transportation and Infrastructure

Input Guidelines for Motor Vehicle Emissions Simulator Model, Volume 3: Final Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 210: Input Guidelines for Motor Vehicle Emissions Simulator Model, Volume 3: Final Report documents the research process for developing the Practitioners’ Handbooks and tools, and provides additional documentation not included in the handbook.NCHRP Web-Only Document 210 Volume 1: Practitioners’ Handbook: Regional Level Inputs explores the development of inputs for a “regional” (county, multicounty, or state) level of application. NCHRP Web-Only Document 210 Volume 2: Practitioners’ Handbook: Project Level Inputs explores the development of inputs for a project level of analysis, using the Project Domain/Scale of the Motor Vehicle Emission Simulator (MOVES) model.Example dataset 1, example dataset 2, example dataset 3, and the MOVES tools are available for download. Please note that these files are large and may take some time to download.Software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively “TRB”) be liable for any loss or damage caused by the installation or operations of this product. TRB makes no representation or warrant of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Input Guidelines for Motor Vehicle Emissions Simulator Model, Volume 1: Practitioners’ Handbook: Regional Level Inputs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 210: Input Guidelines for Motor Vehicle Emissions Simulator Model, Volume 1: Practitioners’ Handbook: Regional Level Inputs provides users of the Motor Vehicle Emissions Simulator Model (MOVES) with tools to help estimate emissions from highway vehicles. Specifically, this handbook provides resource material on developing inputs for a “regional” (county, multicounty, or state) level of application, using the County Domain/Scale of MOVES.In addition to this report, NCHRP Web-Only Document 210 NCHRP Web-Only Document 210 Volume 2: Practitioners’ Handbook: Project Level Inputs explores the development of inputs for a project level of analysis, using the Project Domain/Scale of the Motor Vehicle Emission Simulator (MOVES) model. NCHRP Web-Only Document 210 Volume 3: Final Report documents the research process for developing Volumes 1 and 2, and provides additional documentation not included in the handbook.Example dataset 1, example dataset 2, example dataset 3, and the MOVES tools are available for download. Please note that these files are large and may take some time to download.Software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively “TRB”) be liable for any loss or damage caused by the installation or operations of this product. TRB makes no representation or warrant of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Review of the Research Program of the Partnership for a New Generation of Vehicles: Second Report - Transportation Research Board (The National Academies Press, 1996)
Keywords: Engineering and Technology

Toxicological and Performance Aspects of Oxygenated Motor Vehicle Fuels - National Research Council (The National Academies Press, 1996)
This book reviews a draft report from the federal government that assesses the effects of oxygenated gasoline on public health, air quality, fuel economy, engine performance, and water quality. In addition to evaluating the scientific basis of the report, the book identifies research needed to better understand the impacts of oxygenated fuels. Methyl tertiary-butyl ether (MTBE), which is intended to reduce carbon monoxide pollution during winter, is the most commonly used additive in the federal oxygenated fuels program. MTBE has been implicated in complaints by the public of headaches, coughs, and nausea. Other questions have been raised about reduced fuel economy and engine performance and pollution of ground water due to the use of MTBE in gasoline. The book provides conclusions and recommendations about each major topic addressed in the government's report.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Improving Ground Support Equipment Operational Data for Airport Emissions Modeling - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB’s Airport Cooperative Research Program (ACRP) Report 149: Improving Ground Support Equipment Operational Data for Airport Emissions Modeling provides a potential update to the current data set of default ground support equipment (GSE) fleet and activity used for passenger and cargo aircraft. The report includes a protocol to improve the accuracy and consistency of data collection for airport GSE activity compatible with the Emissions and Dispersion Modeling System (EDMS) and the Aviation Environmental Design Tool (AEDT).
Keywords: Transportation and Infrastructure

Air Pollution, the Automobile, and Public Health - Watson, Ann Y., Sc.D.; Bates, Richard R., M.D.; Kennedy, Donald, Ph.D. (The National Academies Press, 1988)
"The combination of scientific and institutional integrity represented by this book is unusual. It should be a model for future endeavors to help quantify environmental risk as a basis for good decisionmaking." —William D. Ruckelshaus, from the foreword. This volume, prepared under the auspices of the Health Effects Institute, an independent research organization created and funded jointly by the Environmental Protection Agency and the automobile industry, brings together experts on atmospheric exposure and on the biological effects of toxic substances to examine what is known—and not known—about the human health risks of automotive emissions.
Keywords: Environment and Environmental Studies

Urban Forestry: Toward an Ecosystem Services Research Agenda: A Workshop Summary - National Research Council (The National Academies Press, 2013)
Much of the ecological research in the past decades has focused on rural or wilderness areas. Today, however, ecological research has been taking place in our cities, where our everyday decisions can have profound effects on our environment. This research, or urban ecology, includes an important element, trees. Trees have had a variety of environmental benefits for our environment including the sequestering carbon, reducing urban heat island effects, providing vital habitat for wildlife, and making nature accessible. These benefits have important impacts on the physical, socio-economic, and mental health of humans as well. Being exposed to trees has been shown to enhance social cohesion, improve health and recreational opportunities, and increase real estate values. In order to gain more knowledge into this urban forestry, the National Academy of Sciences (NAS) held a workshop February 25-26, 2013. The workshop brought together more than 100 people with various interests in urban forestry research to share information and perspectives, foster communication across specific areas of ecosystem service research, and consider integrated approaches that cut across these realms. The workshop specifically examined current capabilities to characterize and quantify the benefits, key gaps in our understanding, the challenges of planning urban forests in a way that optimizes multiple ecosystem services and more.
Keywords: Earth Sciences

Industrial Environmental Performance Metrics: Challenges and Opportunities (The National Academies Press, 1999)
Industrial Environmental Performance Metrics is a corporate-focused analysis that brings clarity and practicality to the complex issues of environmental metrics in industry. The book examines the metrics implications to businesses as their responsibilities expand beyond the factory gate—upstream to suppliers and downstream to products and services. It examines implications that arise from greater demand for comparability of metrics among businesses by the investment community and environmental interest groups. The controversy over what sustainable development means for businesses is also addressed. Industrial Environmental Performance Metrics identifies the most useful metrics based on case studies from four industries—automotive, chemical, electronics, and pulp and paper—and includes specific corporate examples. It contains goals and recommendations for public and private sector players interested in encouraging the broader use of metrics to improve industrial environmental performance and those interested in addressing the tough issues of prioritization, weighting of metrics for meaningful comparability, and the longer term metrics needs presented by sustainable development.
Keywords: Environment and Environmental Studies; Industry and Labor

Meeting the Challenges of Megacities in the Developing World: A Collection of Working Papers (The National Academies Press, 1996)
Cities in developing countries are experiencing unprecedented population growth, which is exacerbating their already substantial problems in providing shelter and basic services. This volume draws on the significant advances in technologies and management strategies made in recent decades to suggest ways to improve urban life and services, especially for the poor. Four challenges to developing countries' megacities are addressed: labor markets, housing, water and sanitation, and transportation, along with a synthesis of general thinking on how to meet megacity challenges and be competitive in the twenty-first century.
Keywords: Behavioral and Social Sciences; Earth Sciences

Automotive Fuel Economy: How Far Can We Go? - National Research Council (The National Academies Press, 1992)
This volume presents realistic estimates for the level of fuel economy that is achievable in the next decade for cars and light trucks made in the United States and Canada. A source of objective and comprehensive information on the topic, this book takes into account real-world factors such as the financial conditions in the automotive industry, costs and benefits to consumers, and marketability of high-efficiency vehicles. The committee is composed of experts from the fields of science, technology, finance, and regulation and offers practical evaluations of technological improvements that could contribute to increased fuel efficiency. The volume also examines potential barriers to improvement, such as high production costs, regulations on safety and emissions, and consumer preferences. This practical book is of considerable interest to car and light truck manufacturers, policymakers, federal and state agencies, and the public.
Keywords: Transportation and Infrastructure; Energy and Energy Conservation

Critical Technologies: The Role of Chemistry and Chemical Engineering (The National Academies Press, 1992)

Testing and Evaluation of Standoff Chemical Agent Detectors - National Research Council (The National Academies Press, 2003)
The report provides an independent assessment of suitable test protocols that might be useful and reliable for the testing and evaluation of standoff chemical agent detectors. The report proposes two testing protocols, one for passive detectors and one for active detectors, to help ensure the reliable detection of a release of chemical warfare agents. The report determined that testing these detectors by release of chemical warfare agents into the atmosphere would not provide additional useful information on the effectiveness of these detectors than would a rigorous testing protocol using chemical agents in the laboratory combined with atmospheric release of simulated chemical warfare agents.
Keywords: Environment and Environmental Studies; Conflict and Security Issues

Review of the 21st Century Truck Partnership - National Research Council (The National Academies Press, 2008)
The 21st Century Truck Partnership (21CTP), a cooperative research and development partnership formed by four federal agencies with 15 industrial partners, was launched in the year 2000 with high hopes that it would dramatically advance the technologies used in trucks and buses, yielding a cleaner, safer, more efficient generation of vehicles.
Keywords: Transportation and Infrastructure; Energy and Energy Conservation

Review of the Research and Development Plan for the Office of Advanced Automotive Technologies - National Research Council (The National Academies Press, 1998)
Keywords: Transportation and Infrastructure; Energy and Energy Conservation

Keeping Pace with Science and Engineering: Case Studies in Environmental Regulation - National Academy of Engineering (The National Academies Press, 1993)
The technical basis of environmental regulation is always at the edge of scientific and engineering understanding. As knowledge improves, questions will inevitably arise about past decisions. Understanding how the regulatory system accommodates changing scientific and engineering knowledge is vital for achieving environmental values. In this new volume, seven case studies shed light on the interplay between environmental regulation and scientific and engineering understanding, with practical conclusions on how science and engineering should be used for more sound and timely regulatory decision making. The book provides helpful timelines of scientific and regulatory developments for the cases, which include:
Keywords: Environment and Environmental Studies

Review of the Bureau of Ocean Energy Management "Air Quality Modeling in the Gulf of Mexico Region" Study - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Emissions associated with oil and gas exploration, development, and production on the Gulf waters can result in increased levels of air pollutants that contribute to a range of air quality impacts in the Gulf of Mexico Region (GOMR). “Criteria air pollutants”, such as carbon monoxide, lead, nitrogen dioxide, ozone, particulate matter, and sulfur dioxide, are considered harmful to public health and the environment. The Bureau of Ocean Energy Management (BOEM) manages the U.S. outer continental shelf oil and gas resources and is required to help manage air quality in the GOMR.
Keywords: Environment and Environmental Studies; Earth Sciences

Long-Term Health Consequences of Exposure to Burn Pits in Iraq and Afghanistan - Institute of Medicine (The National Academies Press, 2011)
Many veterans returning from the conflicts in Iraq and Afghanistan have health problems they believe are related to their exposure to the smoke from the burning of waste in open-air "burn pits" on military bases. Particular controversy surrounds the burn pit used to dispose of solid waste at Joint Base Balad in Iraq, which burned up to 200 tons of waste per day in 2007. The Department of Veterans Affairs asked the IOM to form a committee to determine the long-term health effects from exposure to these burn pits. Insufficient evidence prevented the IOM committee from developing firm conclusions. This report, therefore, recommends that, along with more efficient data-gathering methods, a study be conducted that would evaluate the health status of service members from their time of deployment over many years to determine their incidence of chronic diseases.
Keywords: Health and Medicine; Environment and Environmental Studies

Curbing Gridlock: Peak-Period Fees to Relieve Traffic Congestion -- Special Report 242 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 1994)
TRB Special Report 242 - Curbing Gridlock: Peak-Period Fees to Relieve Traffic Congestion examines public perseption of congestion pricing. Although road users pay fuel taxes to support the costs of building and maintaining roads, most people view roads as free.Traffic congestion frustrates millions of motorists daily and imposes economic costs in the 50 largest urban areas in excess of $70 billion annually; however, adding highway capacity to allow free-flow traffic is problematic for environmental and other reasons. Economists have long argued that some direct pricing mechanism for highway use would help allocate demand on existing facilities more efficiently by shifting some road users to offpeak hours, when plenty of capacity is usually available. As everyone who drives in peak periods knows, too many people are trying to travel within too limited a space at these times.In the private sector, such peak demand is managed through pricing. At least until recently, however, proposals for peak-period pricing of road use have been dismissed as impractical because of the difficulty of charging users efficiently. Today, electronic toll collection has made it possible to charge users varying prices with considerable efficiency without invading privacy. Now that variable pricing of road use has become technically feasible, the debate has shifted to questions of effectiveness and political acceptability.Economic theory and analytical modeling predict that variable pricing would reduce congestion. The effect can be illustrated by the example of a freeway on which motorists encounter stop-and-go travel. In such a situation, a reduction of only a few percentage points in the number of motorists in the traffic stream can return traffic to free flow. Of course, most motorists would be reluctant or unable to shift their travel times, but those who would adjust their work schedules or be flexible in other ways could shift to off-peak periods, and the result would be net economic and environmental benefits to society. Those traveling in peak periods would have to pay considerable fees, but these revenues could be used to provide more capacity or to compensate those groups hurt economically by such a policy.Since passage of the Intermodal Surface Transportation Efficiency Act of 1991 (ISTEA), federal policy has reflected appropriate caution with regard to advancing alternative pricing concepts by encouraging and funding experimentation at the local level, an approach the committee supported and recommended. Many jurisdictions are considering or engaging in experiments such as pricing underused high-occupancy vehicle lanes, offering discounts on toll facilities for off-peak travel, and increasing parking fees. Preliminary results of these efforts are encouraging and may help gain public acceptance for wider application of such approaches. Although still far from being realized in the mainstream of transportation programs, road pricing may yet become a tool for managing an ever-growing demand with a limited supply.The report was produced in a two volume set. Download Volume 2: Commissioned Papers.
Keywords: Transportation and Infrastructure

Models in Environmental Regulatory Decision Making - National Research Council (The National Academies Press, 2007)
Many regulations issued by the U.S. Environmental Protection Agency (EPA) are based on the results of computer models. Models help EPA explain environmental phenomena in settings where direct observations are limited or unavailable, and anticipate the effects of agency policies on the environment, human health and the economy. Given the critical role played by models, the EPA asked the National Research Council to assess scientific issues related to the agency's selection and use of models in its decisions. The book recommends a series of guidelines and principles for improving agency models and decision-making processes. The centerpiece of the book's recommended vision is a life-cycle approach to model evaluation which includes peer review, corroboration of results, and other activities. This will enhance the agency's ability to respond to requirements from a 2001 law on information quality and improve policy development and implementation.
Keywords: Environment and Environmental Studies; Policy for Science and Technology

Memorial Tributes: Volume 10 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2002)
This is the 10th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964.
Keywords: Biography and Autobiography

Review of the Research Program of the Partnership for a New Generation of Vehicles: Third Report - National Research Council (The National Academies Press, 1997)
This book examines the state of development and research progress of technologies being considered for a new generation of vehicles that could achieve up to three times the fuel economy of comparable 1994 family sedans. It addresses compression ignition direct injection engines, fuel cells, gas turbines, batteries, flywheels, ultracapacitors, and power electronics being developed by the Partnership for a New Generation of Vehicles—a cooperative research and development program between the U.S. government and the U.S. Council for Automotive Research. The book assesses the relevance of the ongoing research to PNGV's goals and schedule and addresses several broad program issues such as government efforts to anticipate infrastructure issues, the leverage of foreign technology, and the program's adequacy and balance.
Keywords: Transportation and Infrastructure; Energy and Energy Conservation

Airport Ground Support Equipment (GSE): Emission Reduction Strategies, Inventory, and Tutorial - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Airport Cooperative Research Program (ACRP) Report 78: Airport Ground Support Equipment (GSE): Emission Reduction Strategies, Inventory, and Tutorial is designed to help assess and mitigate the contribution of ground support equipment (GSE) to air quality impacts at airports.The report presents an inventory of GSE at airports, identifies potential strategies to reduce emissions from powered GSE, and provides a tutorial that describes GSE operations and emission reduction technologies for use by GSE owners and operators.The tutorial is a user-friendly, interactive, self-paced, stand-alone tool that is designed to provide a better understanding of GSE, its operations, applicable federal environmental regulations, and potential approaches to reduce GSE emissions.The tutorial is structured in three modules: GSE Basics, Emissions Reduction Approaches and Case Studies, and Converting to Cleaner GSE. The tutorial is on a CD-ROM that is included with the print version the report.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Effectiveness of the United States Advanced Battery Consortium as a Government-Industry Partnership - National Research Council (The National Academies Press, 1998)
This study by the National Research Council (NRC) was requested by DOE's Office of Advanced Automotive Technologies. The study focuses on the processes used by the USABC to select, evaluate, and manage R&D projects on EV batteries in Phases I and II of the program.
Keywords: Industry and Labor; Engineering and Technology

Energy: Production, Consumption, and Consequences - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1990)
Energy provides a fresh, multidisciplinary approach to energy analysis. Leading experts from diverse fields examine the evolving structure of our energy system from several perspectives. They explore the changing patterns of supply and demand, offer insights into the forces that are driving the changes, and discuss energy planning strategies that take advantage of such insights. The book addresses several major issues, including the growing vulnerabilities in the U.S. energy system, the influence of technological change, and the role of electricity in meeting social objectives. The strongest of the book's themes is the growing influence of environmental concerns on the global energy system.
Keywords: Energy and Energy Conservation

Review of the Research Program of the Partnership for a New Generation of Vehicles: Fourth Report - National Research Council (The National Academies Press, 1998)
This book examines the state of development and research progress of technologies being considered for a new generation of vehicles that could achieve up to three times the fuel economy of comparable 1994 family sedans. It addresses advanced automotive technologies including engines, fuel cells, batteries, flywheels, power electronics, and lightweight materials being developed by the Partnership for a New Generation of Vehicles—a cooperative research and development program between the U.S. government and the U.S. Council for Automotive Research. The book assesses the relevance of the ongoing research to PNGV's goals and schedule, the program's adequacy and balance, and addresses several issues such as the benefits of hybrid versus nonhybrid vehicles and the importance of the sports utility vehicle market.
Keywords: Transportation and Infrastructure; Energy and Energy Conservation; Engineering and Technology

Review of the NARSTO Draft Report: NARSTO Assessment of the Atmospheric Science on Particulate Matter - National Research Council (The National Academies Press, 2002)
Keywords: Environment and Environmental Studies

Strengthening Post-Hurricane Supply Chain Resilience: Observations from Hurricanes Harvey, Irma, and Maria - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Resilient supply chains are crucial to maintaining the consistent delivery of goods and services to the American people. The modern economy has made supply chains more interconnected than ever, while also expanding both their range and fragility. In the third quarter of 2017, Hurricanes Harvey, Irma and Maria revealed some significant vulnerabilities in the national and regional supply chains of Texas, Florida, the U.S. Virgin Islands, and Puerto Rico. The broad impacts and quick succession of these three hurricanes also shed light on the effectiveness of the nation's disaster logistics efforts during response through recovery. Drawing on lessons learned during the 2017 hurricanes, this report explores future strategies to improve supply chain management in disaster situations. This report makes recommendations to strengthen the roles of continuity planning, partnerships between civic leaders with small businesses, and infrastructure investment to ensure that essential supply chains will remain operational in the next major disaster. Focusing on the supply chains food, fuel, water, pharmaceutical, and medical supplies, the recommendations of this report will assist the Federal Emergency Management Agency as well as state and local officials, private sector decision makers, civic leaders, and others who can help ensure that supply chains remain robust and resilient in the face of natural disasters.
Keywords: Conflict and Security Issues; Earth Sciences

Health Impact Assessment of Shale Gas Extraction: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Natural gas extraction from shale formations, which includes hydraulic fracturing, is increasingly in the news as the use of extraction technologies has expanded, rural communities have been transformed seemingly overnight, public awareness has increased, and regulations have been developed. The governmental public health system, which retains primary responsibility for health, was not an early participant in discussions about shale gas extraction; thus public health is lacking critical information about environmental health impacts of these technologies and is limited in its ability to address concerns raised by regulators at the federal and state levels, communities, and workers employed in the shale gas extraction industry. Health Impact Assessment of Shale Gas Extraction is the summary of a workshop convened in 2012 by the Institute of Medicine (IOM) Roundtable on Environmental Health Sciences, Research, and Medicine to discuss the human health impact of shale gas extraction through the lens of a health impact assessment. Eminent scientists, physicians, public health experts, and representatives from government agencies at federal and state levels, from nongovernment organizations, from the business sector, and from interest groups representing the interests of the citizens met to exchange ideas and to inform on hydraulic fracturing as a means of extraction of natural gas. This report examines the state of the science regarding shale gas extraction, the direct and indirect environmental health impacts of shale gas extraction, and the use of health impact assessment as a tool that can help decision makers identify the public health consequences of shale gas extraction.
Keywords: Health and Medicine

Atmospheric Change and the North American Transportation Sector: Summary of a Trilateral Workshop (The National Academies Press, 1998)
Keywords: Environment and Environmental Studies

Observing Weather and Climate from the Ground Up: A Nationwide Network of Networks - National Research Council (The National Academies Press, 2009)
Detailed weather observations on local and regional levels are essential to a range of needs from forecasting tornadoes to making decisions that affect energy security, public health and safety, transportation, agriculture and all of our economic interests. As technological capabilities have become increasingly affordable, businesses, state and local governments, and individual weather enthusiasts have set up observing systems throughout the United States. However, because there is no national network tying many of these systems together, data collection methods are inconsistent and public accessibility is limited. This book identifies short-term and long-term goals for federal government sponsors and other public and private partners in establishing a coordinated nationwide "network of networks" of weather and climate observations.
Keywords: Earth Sciences; Space and Aeronautics

Multimodal Transportation Planning Data: Final Report - Transportation Research Board (The National Academies Press, 1997)

Hidden Costs of Energy: Unpriced Consequences of Energy Production and Use - National Research Council (The National Academies Press, 2010)
Despite the many benefits of energy, most of which are reflected in energy market prices, the production, distribution, and use of energy causes negative effects. Many of these negative effects are not reflected in energy market prices. When market failures like this occur, there may be a case for government interventions in the form of regulations, taxes, fees, tradable permits, or other instruments that will motivate recognition of these external or hidden costs. The Hidden Costs of Energy defines and evaluates key external costs and benefits that are associated with the production, distribution, and use of energy, but are not reflected in market prices. The damage estimates presented are substantial and reflect damages from air pollution associated with electricity generation, motor vehicle transportation, and heat generation. The book also considers other effects not quantified in dollar amounts, such as damages from climate change, effects of some air pollutants such as mercury, and risks to national security. While not a comprehensive guide to policy, this analysis indicates that major initiatives to further reduce other emissions, improve energy efficiency, or shift to a cleaner electricity generating mix could substantially reduce the damages of external effects. A first step in minimizing the adverse consequences of new energy technologies is to better understand these external effects and damages. The Hidden Costs of Energy will therefore be a vital informational tool for government policy makers, scientists, and economists in even the earliest stages of research and development on energy technologies.
Keywords: Energy and Energy Conservation

New Source Review for Stationary Sources of Air Pollution - National Research Council (The National Academies Press, 2006)
The Clean Air Act established a pair of programs—known as New Source Review (NSR)—that regulate large stationary sources of air pollution, such as factories and electricity-generating facilities. Congress then asked the National Research Council to estimate the effects of NSR rule changes made in 2002 and 2003 in terms of the effects on emissions and human health, and changes in operating efficiency (including energy efficiency), pollution prevention, and pollution-control activities. New Source Review for Stationary Sources of Air Pollution provides insights into the potential effects of the rule changes on national emissions from the electric power industry. Although this book focuses on the 2002 and 2003 rules, its analytic framework applies to other possible changes in NSR and to other regulatory contexts. Helpful, in that it outlines the data-collection efforts needed to assess the impact of the NSR rules, the book recommends EPA and other government agencies undertake and sustain the recommended methods.
Keywords: Environment and Environmental Studies

Interim Report of the Committee on Changes in New Source Review Programs for Stationary Sources of Air Pollutants - National Research Council (The National Academies Press, 2005)
Keywords: Environment and Environmental Studies

Quantifying Aircraft Lead Emissions at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB’s Airport Cooperative Research Program (ACRP) Web-Only Document 21: Quantifying Aircraft Lead Emissions at Airports reviews methods for quantifying aircraft-related lead emissions.ACRP Report 133: Best Practices Guidebook for Preparing Lead Emission Inventories from Piston-Powered Aircraft with the Emission Inventory Analysis Tool provides guidance for quantifying airport lead emissions so that airports may assess aircraft-related lead emissions at their facilities.
Keywords: Transportation and Infrastructure

Biobased Industrial Products: Priorities for Research and Commercialization - National Research Council (The National Academies Press, 2000)
Petroleum-based industrial products have gradually replaced products derived from biological materials. However, biologically based products are making a comeback—because of a threefold increase in farm productivity and new technologies. Biobased Industrial Products envisions a biobased industrial future, where starch will be used to make biopolymers and vegetable oils will become a routine component in lubricants and detergents. Biobased Industrial Products overviews the U.S. land resources available for agricultural production, summarizes plant materials currently produced, and describes prospects for increasing varieties and yields. The committee discusses the concept of the biorefinery and outlines proven and potential thermal, mechanical, and chemical technologies for conversion of natural resources to industrial applications. The committee also illustrates the developmental dynamics of biobased products through existing examples, as well as products still on the drawing board, and it identifies priorities for research and development.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Traveler Response to Transportation System Changes Handbook, Third Edition: Chapter 3, Park-and-Ride/Pool - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Report 95: Chapter 3 – Park-and-Ride/Pool examines travel demand and related aspects of providing and supporting park-and-ride and park-and-pool facilities.The Traveler Response to Transportation System Changes Handbook consists of these Chapter 1 introductory materials and 15 stand-alone published topic area chapters. Each topic area chapter provides traveler response findings including supportive information and interpretation, and also includes case studies and a bibliography consisting of the references utilized as sources.
Keywords: Transportation and Infrastructure

Renewable Fuel Standard: Potential Economic and Environmental Effects of U.S. Biofuel Policy - National Research Council (The National Academies Press, 2011)
In the United States, we have come to depend on plentiful and inexpensive energy to support our economy and lifestyles. In recent years, many questions have been raised regarding the sustainability of our current pattern of high consumption of nonrenewable energy and its environmental consequences. Further, because the United States imports about 55 percent of the nation's consumption of crude oil, there are additional concerns about the security of supply. Hence, efforts are being made to find alternatives to our current pathway, including greater energy efficiency and use of energy sources that could lower greenhouse gas (GHG) emissions such as nuclear and renewable sources, including solar, wind, geothermal, and biofuels. The United States has a long history with biofuels and the nation is on a course charted to achieve a substantial increase in biofuels. Renewable Fuel Standard evaluates the economic and environmental consequences of increasing biofuels production as a result of Renewable Fuels Standard, as amended by EISA (RFS2). The report describes biofuels produced in 2010 and those projected to be produced and consumed by 2022, reviews model projections and other estimates of the relative impact on the prices of land, and discusses the potential environmental harm and benefits of biofuels production and the barriers to achieving the RFS2 consumption mandate. Policy makers, investors, leaders in the transportation sector, and others with concerns for the environment, economy, and energy security can rely on the recommendations provided in this report.
Keywords: Environment and Environmental Studies; Energy and Energy Conservation

Technologies and Approaches to Reducing the Fuel Consumption of Medium- and Heavy-Duty Vehicles - Transportation Research Board; National Research Council (The National Academies Press, 2010)
Technologies and Approaches to Reducing the Fuel Consumption of Medium- and Heavy-Duty Vehicles evaluates various technologies and methods that could improve the fuel economy of medium- and heavy-duty vehicles, such as tractor-trailers, transit buses, and work trucks. The book also recommends approaches that federal agencies could use to regulate these vehicles' fuel consumption. Currently there are no fuel consumption standards for such vehicles, which account for about 26 percent of the transportation fuel used in the U.S.
Keywords: Energy and Energy Conservation; Transportation and Infrastructure

Carbon Management: Implications for R&D in the Chemical Sciences and Technology - National Research Council (The National Academies Press, 2001)
Considerable international concerns exist about global climate change and its relationship to the growing use of fossil fuels. Carbon dioxide is released by chemical reactions that are employed to extract energy from fuels, and any regulatory policy limiting the amount of CO2 that could be released from sequestered sources or from energy-generating reactions will require substantial involvement of the chemical sciences and technology R&D community. Much of the public debate has been focused on the question of whether global climate change is occurring and, if so, whether it is anthropogenic, but these questions were outside the scope of the workshop, which instead focused on the question of how to respond to a possible national policy of carbon management. Previous discussion of the latter topic has focused on technological, economic, and ecological aspects and on earth science challenges, but the fundamental science has received little attention. This workshop was designed to gather information that could inform the Chemical Sciences Roundtable in its discussions of possible roles that the chemical sciences community might play in identifying and addressing underlying chemical questions.
Keywords: Math, Chemistry, and Physics; Energy and Energy Conservation

Effectiveness and Impact of Corporate Average Fuel Economy (CAFE) Standards - Transportation Research Board; National Research Council (The National Academies Press, 2002)
Since CAFE standards were established 25 years ago, there have been significant changes in motor vehicle technology, globalization of the industry, the mix and characteristics of vehicle sales, production capacity, and other factors. This volume evaluates the implications of these changes as well as changes anticipated in the next few years, on the need for CAFE, as well as the stringency and/or structure of the CAFE program in future years.
Keywords: Energy and Energy Conservation; Transportation and Infrastructure

Fuels to Drive Our Future - National Research Council (The National Academies Press, 1990)
The American love affair with the automobile is powered by gasoline and diesel fuel, both produced from petroleum. But experts are turning more of their attention to alternative sources of liquid transportation fuels, as concerns mount about U.S. dependence on foreign oil, falling domestic oil production, and the environment. This book explores the potential for producing liquid transportation fuels by enhanced oil recovery from existing reservoirs, and processing resources such as coal, oil shale, tar sands, natural gas, and other promising approaches. Fuels to Drive Our Future draws together relevant geological, technical, economic, and environmental factors and recommends specific directions for U.S. research and development efforts on alternative fuel sources. Of special interest is the book's benchmark cost analysis comparing several major alternative fuel production processes. This volume will be of special interest to executives and engineers in the automotive and fuel industries, policymakers, environmental and alternative fuel specialists, energy economists, and researchers.
Keywords: Energy and Energy Conservation

Review of the Research Program of the U.S. DRIVE Partnership: Fifth Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Review of the Research Program of the U.S. DRIVE Partnership: Fifth Report follows on four previous reviews of the FreedomCAR and Fuel Partnership, which was the predecessor of the U.S. DRIVE Partnership. The U.S. DRIVE (Driving Research and Innovation for Vehicle Efficiency and Energy Sustainability) vision, according to the charter of the Partnership, is this: American consumers have a broad range of affordable personal transportation choices that reduce petroleum consumption and significantly reduce harmful emissions from the transportation sector. Its mission is as follows: accelerate the development of pre-competitive and innovative technologies to enable a full range of efficient and clean advanced light-duty vehicles (LDVs), as well as related energy infrastructure. The Partnership focuses on precompetitive research and development (R&D) that can help to accelerate the emergence of advanced technologies to be commercialization-feasible. The guidance for the work of the U.S. DRIVE Partnership as well as the priority setting and targets for needed research are provided by joint industry/government technical teams. This structure has been demonstrated to be an effective means of identifying high-priority, long-term precompetitive research needs for each technology with which the Partnership is involved. Technical areas in which research and development as well as technology validation programs have been pursued include the following: internal combustion engines (ICEs) potentially operating on conventional and various alternative fuels, automotive fuel cell power systems, hydrogen storage systems (especially onboard vehicles), batteries and other forms of electrochemical energy storage, electric propulsion systems, hydrogen production and delivery, and materials leading to vehicle weight reductions.
Keywords: Energy and Energy Conservation; Transportation and Infrastructure

Sustainable Development of Algal Biofuels in the United States - National Research Council (The National Academies Press, 2012)
Biofuels made from algae are gaining attention as a domestic source of renewable fuel. However, with current technologies, scaling up production of algal biofuels to meet even 5 percent of U.S. transportation fuel needs could create unsustainable demands for energy, water, and nutrient resources. Continued research and development could yield innovations to address these challenges, but determining if algal biofuel is a viable fuel alternative will involve comparing the environmental, economic and social impacts of algal biofuel production and use to those associated with petroleum-based fuels and other fuel sources. Sustainable Development of Algal Biofuels was produced at the request of the U.S. Department of Energy.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies; Biology and Life Sciences

Environmental Performance Measures for State Departments of Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB's National Cooperative Highway Research Program (NCHRP) Report 809: Environmental Performance Measures for State Departments of Transportation identifies potential environmental performance measures that may be integrated into a transportation agency's performance management program. The report explores relationships between agency activities and environmental outcomes.A spreadsheet-based “Measure Calculation Tool” helps transportation agencies implement performance measures that were outlined in the report. The tool can be used to record the component data needed to calculate the measures.
Keywords: Transportation and Infrastructure

Assessment of Fuel Economy Technologies for Light-Duty Vehicles - National Research Council (The National Academies Press, 2011)
Various combinations of commercially available technologies could greatly reduce fuel consumption in passenger cars, sport-utility vehicles, minivans, and other light-duty vehicles without compromising vehicle performance or safety. Assessment of Technologies for Improving Light Duty Vehicle Fuel Economy estimates the potential fuel savings and costs to consumers of available technology combinations for three types of engines: spark-ignition gasoline, compression-ignition diesel, and hybrid.
Keywords: Energy and Energy Conservation; Transportation and Infrastructure

The Congestion Mitigation and Air Quality Improvement Program: Assessing 10 Years of Experience -- Special Report 264 - Transportation Research Board (The National Academies Press, 2002)
TRB Special Report 264 - Congestion Mitigation and Air Quality Improvement Program: Assessing 10 Years of Experience recommends that Congress retain the sole federal surface transportation program that funds projects to reduce pollution and traffic congestion in areas that must comply with national air quality standards.
Keywords: Environment and Environmental Studies

A Framework for Assessing Effects of the Food System - Institute of Medicine; National Research Council (The National Academies Press, 2015)
How we produce and consume food has a bigger impact on Americans' well-being than any other human activity. The food industry is the largest sector of our economy; food touches everything from our health to the environment, climate change, economic inequality, and the federal budget. From the earliest developments of agriculture, a major goal has been to attain sufficient foods that provide the energy and the nutrients needed for a healthy, active life. Over time, food production, processing, marketing, and consumption have evolved and become highly complex. The challenges of improving the food system in the 21st century will require systemic approaches that take full account of social, economic, ecological, and evolutionary factors. Policy or business interventions involving a segment of the food system often have consequences beyond the original issue the intervention was meant to address. A Framework for Assessing Effects of the Food System develops an analytical framework for assessing effects associated with the ways in which food is grown, processed, distributed, marketed, retailed, and consumed in the United States. The framework will allow users to recognize effects across the full food system, consider all domains and dimensions of effects, account for systems dynamics and complexities, and choose appropriate methods for analysis. This report provides example applications of the framework based on complex questions that are currently under debate: consumption of a healthy and safe diet, food security, animal welfare, and preserving the environment and its resources. A Framework for Assessing Effects of the Food System describes the U.S. food system and provides a brief history of its evolution into the current system. This report identifies some of the real and potential implications of the current system in terms of its health, environmental, and socioeconomic effects along with a sense for the complexities of the system, potential metrics, and some of the data needs that are required to assess the effects. The overview of the food system and the framework described in this report will be an essential resource for decision makers, researchers, and others to examine the possible impacts of alternative policies or agricultural or food processing practices.
Keywords: Food and Nutrition; Agriculture

Urbanization, Energy, and Air Pollution in China: The Challenges Ahead: Proceedings of a Symposium - National Research Council; National Academy of Engineering (The National Academies Press, 2004)
In October 2003, a group of experts met in Beijing under the auspices of the Chinese Academy of Sciences, Chinese Academy of Engineering, and National Academy of Engineering (NAE)/National Research Council (NRC) of the National Academies to continue a dialogue and eventually chart a rational course of energy use in China. This collection of papers is intended to introduce the reader to the complicated problems of urban air pollution and energy choices in China.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Science and Judgment in Risk Assessment - National Research Council (The National Academies Press, 1994)
The public depends on competent risk assessment from the federal government and the scientific community to grapple with the threat of pollution. When risk reports turn out to be overblown—or when risks are overlooked—public skepticism abounds. This comprehensive and readable book explores how the U.S. Environmental Protection Agency (EPA) can improve its risk assessment practices, with a focus on implementation of the 1990 Clean Air Act Amendments. With a wealth of detailed information, pertinent examples, and revealing analysis, the volume explores the "default option" and other basic concepts. It offers two views of EPA operations: The first examines how EPA currently assesses exposure to hazardous air pollutants, evaluates the toxicity of a substance, and characterizes the risk to the public. The second, more holistic, view explores how EPA can improve in several critical areas of risk assessment by focusing on cross-cutting themes and incorporating more scientific judgment. This comprehensive volume will be important to the EPA and other agencies, risk managers, environmental advocates, scientists, faculty, students, and concerned individuals.
Keywords: Environment and Environmental Studies

Case Studies of Truck Activity Data for Emissions Modeling - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
NCHRP Web-Only Document 261: Case Studies of Truck Activity Data for Emissions Modeling consists of seven case studies that are appendices A to G of NCHRP Report 909: Guide to Truck Activity Data for Emissions Modeling.NCHRP Research Report 909 explores methods, procedures, and data sets needed to capture commercial vehicle activity, vehicle characteristics, and operations to assist in estimating and forecasting criteria pollutants, air toxics, and greenhouse gas emissions from goods and services movement.NCHRP Research Report 909 is also supplemented by three MS Excel files that contain data from the case studies:Case Studies #1 and #7Case Study #2Case Studies #3, #4, and #6
Keywords: Transportation and Infrastructure

Innovative Practices for Multimodal Planning for Freight and Passengers: Project Bibliography - Transportation Research Board (The National Academies Press, 1995)

Representing Freight in Air Quality and Greenhouse Gas Models - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Freight Cooperative Research Program (NFCRP) Report 4: Representing Freight in Air Quality and Greenhouse Gas Models explores the current methods used to generate air emissions information from all freight transportation activities and their suitability for purposes such as health and climate risk assessments, prioritization of emission reduction activities, and public education.The report highlights the state of the practice, and potential gaps, strengths, and limitations of current emissions data estimates and methods. The report also examines a conceptual model that offers a comprehensive representation of freight activity by all transportation modes and relationships between modes.
Keywords: Transportation and Infrastructure

Energy Futures and Urban Air Pollution: Challenges for China and the United States - National Academy of Engineering; National Research Council (The National Academies Press, 2008)
The United States and China are the top two energy consumers in the world. As a consequence, they are also the top two emitters of numerous air pollutants which have local, regional, and global impacts. Urbanization has led to serious air pollution problems in U.S. and Chinese cities; although U.S. cities continues to face challenges, the lessons they have learned in managing energy use and air quality are relevant to the Chinese experience. This report summarizes current trends, profiles two U.S. and two Chinese cities, and recommends key actions to enable each country to continue to improve urban air quality.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Cost, Effectiveness, and Deployment of Fuel Economy Technologies for Light-Duty Vehicles - National Research Council (The National Academies Press, 2015)
The light-duty vehicle fleet is expected to undergo substantial technological changes over the next several decades. New powertrain designs, alternative fuels, advanced materials and significant changes to the vehicle body are being driven by increasingly stringent fuel economy and greenhouse gas emission standards. By the end of the next decade, cars and light-duty trucks will be more fuel efficient, weigh less, emit less air pollutants, have more safety features, and will be more expensive to purchase relative to current vehicles. Though the gasoline-powered spark ignition engine will continue to be the dominant powertrain configuration even through 2030, such vehicles will be equipped with advanced technologies, materials, electronics and controls, and aerodynamics. And by 2030, the deployment of alternative methods to propel and fuel vehicles and alternative modes of transportation, including autonomous vehicles, will be well underway. What are these new technologies - how will they work, and will some technologies be more effective than others? Written to inform The United States Department of Transportation's National Highway Traffic Safety Administration (NHTSA) and Environmental Protection Agency (EPA) Corporate Average Fuel Economy (CAFE) and greenhouse gas (GHG) emission standards, this new report from the National Research Council is a technical evaluation of costs, benefits, and implementation issues of fuel reduction technologies for next-generation light-duty vehicles. Cost, Effectiveness, and Deployment of Fuel Economy Technologies for Light-Duty Vehicles estimates the cost, potential efficiency improvements, and barriers to commercial deployment of technologies that might be employed from 2020 to 2030. This report describes these promising technologies and makes recommendations for their inclusion on the list of technologies applicable for the 2017-2025 CAFE standards.
Keywords: Energy and Energy Conservation; Engineering and Technology; Transportation and Infrastructure